Control of flow separation - Ang, Wei Qin (2012)
Micro Air Vehicles (MAVs) are often required to operate in small and enclosed spaces at low speeds, and thus, it is important for MAVs to have high manoeuvrability in order to complete their missions. The use of self-activated flaps as a means of enhancing lift at high angles of attack as well as delaying flow separation is an inexpensive and relatively easy addition to improve the performance of MAVs. It is also easy to implement and easy to replace should there be any need of it. As a result, a lot of studies have been done into the usage of self-activated flaps on Micro Air Vehicles.